2019
DOI: 10.1111/1742-6723.13244
|View full text |Cite
|
Sign up to set email alerts
|

Older age is associated with a reduced likelihood of ambulance transport to a trauma centre after major trauma in Perth

Abstract: Objective To describe the characteristics and outcomes of older adult (≥65 years) major trauma patients in comparison with younger adults (16–64 years). To determine whether older age is associated with a reduced likelihood of transport (directly or indirectly) to a major trauma centre and whether this is associated with in‐hospital mortality. Methods A retrospective cohort study of major trauma patients transported to hospital by St John Ambulance paramedics in Perth, Western Australia, between 1 January 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The literature from the United States of America (USA) and Australia show increased rates of under-triage among this population. [3][4][5][6][7][8][9][10][11][12][13][14][15] Under-triage is simply defined as the transportation of severely injured patients to lower-level Trauma Centers (TCs) or other Acute Care (AC) facilitates, as opposed to Major Trauma Centers (MTCs) (equivalent to major trauma service or Level I or II TCs). 16 A number of recent studies in the USA developed trauma triage tools specific for older adults in order to improve early identification and appropriate triage and transportation decisions.…”
Section: Scope Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature from the United States of America (USA) and Australia show increased rates of under-triage among this population. [3][4][5][6][7][8][9][10][11][12][13][14][15] Under-triage is simply defined as the transportation of severely injured patients to lower-level Trauma Centers (TCs) or other Acute Care (AC) facilitates, as opposed to Major Trauma Centers (MTCs) (equivalent to major trauma service or Level I or II TCs). 16 A number of recent studies in the USA developed trauma triage tools specific for older adults in order to improve early identification and appropriate triage and transportation decisions.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…3,5,10,15 accuracy in identifying major trauma among older people 4,6,8,9,11,12,14,17,62 and only few were assessed for their effects on the outcomes, with mortality used as the main outcome measure. 3,5,7,10,13,15,63,64 Other outcomes including disability, complications, costs, LOS, and discharge to home were rarely captured in the assessment of triage tools. 7,10,15,63 No standardized patient outcome measures regarding functional status, quality of life, and wellbeing for older trauma patients were reported in these studies.…”
Section: Prehospital Triage and Outcomesmentioning
confidence: 99%
“…For example, head injuries are more likely to require immediate airway interventions, thus making transport to the nearest hospital more likely 24 . Conversely, it has been shown that older adults with severe injuries are less likely to be transported to a Trauma Centre than younger adults 25,26 . Reasons for this include the ability of older adults to appear deceptively uninjured due to their lack of apparent physiological derangement 27,28 and presence of occult hypoperfusion, which is difficult to identify 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is often the presence of comorbidities, polypharmacy, anticoagulation/antiplatelet therapies and physiologic changes that can alter the response to injury 29 . Concerningly, the undertriaging of older adults increases the odds of mortality 26,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Lift assistance is provided when a person falls, is unable to move and requires physical help to return to a preferred position (13), such as rise from the floor to stand or sit. Alternatively, the patient may be referred to their general practitioner or an allied health service such as a falls clinic (7,11).…”
Section: Ems-attended Falls Reviewmentioning
confidence: 99%